2017
DOI: 10.1371/journal.pone.0179678
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity pneumonitis onset and severity is regulated by CD103 dendritic cell expression

Abstract: BackgroundPulmonary dendritic cells drive lung responses to foreign antigens, including Saccharopolyspora rectivirgula, a causative agent of hypersensitivity pneumonitis. While the airway inflammatory mechanisms involved in hypersensitivity pneumonitis are well described, the mechanisms leading to the break in homeostasis and hypersensitivity pneumonitis onset are not well-described, and could involve CD103+ dendritic cells, which are found at baseline and during inflammatory responses in the lung. However, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
(51 reference statements)
3
13
0
Order By: Relevance
“…In this line of thought, we have previously demonstrated that a single exposure to Saccharopolyspora rectivirgula extract decreases the proportion of lung CD103 + DCs [10], altering the DC balance and likely contributing to the initiation of this hypersensitivity response. However, the exact mechanisms underlying this phenomenon remain unknown.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this line of thought, we have previously demonstrated that a single exposure to Saccharopolyspora rectivirgula extract decreases the proportion of lung CD103 + DCs [10], altering the DC balance and likely contributing to the initiation of this hypersensitivity response. However, the exact mechanisms underlying this phenomenon remain unknown.…”
Section: Introductionmentioning
confidence: 93%
“…CD103 + DC1s and CD11b + DC2s are the major two DC populations in the lung at steady state . As they are functionally different , their simultaneous presence and various complementary functions insure lung homeostasis maintenance by supporting the efficient pulmonary immune response to a variety of stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…These times were chosen since CD103 is still expressed on cDCs at that time following LPS exposure ( Brassard et al., 2019 ), and because the increase in total cells in response to P. aeruginosa is slower than following LPS administration (data not shown). Of note, although CD103 is also present on T cells, they do not play a role in the rapid innate immune response to these agents ( Andrew et al., 1996 ; Bernatchez et al., 2017 ). Following the i.n.…”
Section: Resultsmentioning
confidence: 99%
“…25 Acute immune responses against inhalation of causative antigens is also important for the pathogenesis of HP, including antigen presentation by dendritic cells and Th1/Th17 responses. 26,27 Taking together, the increase of apoA-I concentration in BALF may reflect an anti-inflammatory response locally against inhalation of causative antigens in HP, although the direct secretion of apoA-I by lung cells into BALF has not yet been demonstrated. 12 In contrast, the expression of apoA-I was significantly lower in BALF from patients with chronic HP compared with acute HP.…”
Section: Discussionmentioning
confidence: 99%
“…ApoA‐I can attenuate antigen presentation and T‐cell activation by the decrease of major histocompatibility complex class II proteins in ovalbumin allergic mice model 25 . Acute immune responses against inhalation of causative antigens is also important for the pathogenesis of HP, including antigen presentation by dendritic cells and Th1/Th17 responses 26,27 . Taking together, the increase of apoA‐I concentration in BALF may reflect an anti‐inflammatory response locally against inhalation of causative antigens in HP, although the direct secretion of apoA‐I by lung cells into BALF has not yet been demonstrated 12 .…”
Section: Discussionmentioning
confidence: 99%